Green Homes Need Green Homeowners: Investigating the Predictive Power of Environmental Concern through the Lens of Theory of Planned Behaviour - Nelson Lajuni; Noraini Abdullah; Yusman Yacob; Franklin Hazley Lai (2018)
This study attempts to examine the intention of homebuyers to purchase green homes in Sabah. The extended Theory of Planned Behavior (TPB) served as a framework for identifying the drivers of green purchasing behavior and their relative importance. Specifically, the objective of this study is to examine the effect of attitude, subjective norms and perceived behavioural control on intention to purchase green house. In addition to that, environmental concern and perceived self-identity are incorporated into the model as the antecedents, influencing not only one’s attitude towards a green home, but also directly towards intention to purchase green homes. Data were collected from potential homebuyers in Sabah, and analysed using Partial Least Squares Structural Equation Modelling. The findings suggested that all claimed hypotheses were supported except for social norms predictor. Implication and contribution of the study were discussed to justify the significance of this research.